The translatability of animal models for clinical development: biomarkers and disease models - Wendler, Alexandra; Wehling, Martin (Current opinion in pharmacology, 2010)
Translational science in medicine describes the transfer of basic in vitro and in vivo research into human applications. Animal models are important tools in translational science, and several different approaches such as genetically engineered animals, xenograft models, inbred strains and disease induction models are available for many diseases. Biomarkers are defined as any measurable parameters of biological processes. This includes disease pathophysiology and the impact of interventions thereon. Biomarkers represent the most important tool of translational science in medicine. Therefore, the development of biomarkers, which are useful and accessible both in animals and in humans, represents an important focus of translational activities. Imaging, for example, is translationally ideal as the readouts in disease models and patients are the same or at least very similar. Despite several approved animal models, the majority of compounds tested successfully in animals still fail to be successfully applied to human diseases. To reduce this rate of failure, animal models better resembling the human situation are needed. A new scoring system for the assessment of translatability is discussed; it facilitates the judgement on the predictivity of results from a given animal model regarding human translation by the weighed answers to important data features. These include robust animal data in more than one species, related human data and accessibility.